Perlindungan Hukum Terhadap Anak Sebagai Kurir Narkotika - Asep Syarifuddin Hidayat; Samul Anam; Muhammad Ishar Helmi (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2018)
Abstract.Children have an important role in the life of society and the state, because of their position as the nation's successor. Therefore, children have the potential to play an active role in preserving the life of the nation, in order to realize the goal of forming a government that protects citizens. The abuse of narcotics by children is currently a concern of many people and is constantly being discussed and published. In fact, the problem of narcotics abuse is of concern to various groups, moreover the involvement of children as narcotics couriers which is a series of evil consensus in carrying out illegal drug trafficking. In the capacity of children who are used as couriers is one thing that is so alarming that the child will face the law, and is classified as having committed narcotics crimes. With the limited ability of children and their imperfections, it needs to be a concern of law enforcement officials in the application of punishment for the child who is the perpetrator of the narcotics crime.Keywords: Legal Protection, Children, Narcotics Courier. Abstrak. Anak mempunyai peranan yang penting di dalam kehidupan bermasyarakat dan bernegara, karena kedudukannya sebagai penerus bangsa. Oleh karena itu, anak mempunyai potensi untuk berperan aktif menjaga kelestarian kehidupan bangsa, guna mewujudkan tujuan pembentukan suatu pemerintah yang melindungi warga negara. Penyalahgunaan narkotika oleh anak saat ini menjadi perhatian banyak orang dan terus menerus dibicarakan dan dipublikasikan. Bahkan, masalah penyalahgunaan narkotika menjadi perhatian berbagai kalangan, apalagi adanya keterlibatan anak sebagai kurir narkotika yang merupakan rangkaian permufakatan jahat dalam menjalankan peredaran narkotika secara illegal. Dalam kapasitas anak yang dijadikan kurir merupakan satu hal yang begitu memprihatinkan dimana anak tersebut akan berhadapan dengan hukum, dan tergolong telah melakukan tindak pidana narkotika. Dengan keterbatasan kemampuan anak dan ketidaksesempurnaannya, maka perlu menjadi perhatian aparat penegak hukum dalam penerapan pemidanaan bagi anak pelaku tindak pidana narkotika tersebut.Kata Kunci: Perlindungan Hukum, Anak, Kurir Narkotika.